Efficacy of Acupuncture Treatment for Postprandial Distress Syndrome: A Systematic Review and Meta-Analysis - Jihang Du; Yinhao Feng; Qiang Yuan; Haiping Gong; Jie An; Liu Wu; Qian Dai; Bojun Xu; Haozhong Wang; Jian Luo (Journal of Immunology Research)
Objective. This systematic review and meta-analysis was conducted to assess the efficacy of acupuncture treatment for postprandial distress syndrome (PDS). Methods. Search the Web of Science, the Cochrane Library, PubMed, and Embase databases with acupuncture randomized controlled trials for the treatment of patients with PDS. Strictly according to inclusion and exclusion quality assessment standards, the qualified ones are used to study the optimum extraction and data by two independent reviewers. Stata 15.0 software was used for meta-analysis. Result. We initially identified 63 studies, of which five (1253 participants) were eventually included in our analysis. There were 643 cases in the experimental group and 610 cases in the control group. Acupuncture had a significant effect on the total therapeutic effect (OTE) at week 4 (OR 4.74, 95% CI 02.88-7.83, Z=6.10, P=0<0.05). Significantly improved NDI (Nepean dyspepsia index) scores of PDS patients at week 4 (SMD 0.61, 95% CI 0.48 to 0.74). Significantly improved NDI scores in PDS patients at week 16 (SMD 0.49, 95% CI 0.27 to 0.71). After acupuncture treatment, the SID (dyspepsia symptom index) score of PDS patients decreased significantly at week 4 (SMD-0.52, 95% CI -0.73 to -0.32) and week 16 (SMD-0.59, 95% CI -0.81 to -0.36). Postprandial satiety scores (SMD-0.63, 95% CI -0.76 to -0.50) and early satiety scores (SMD-0.51, 95% CI -0.64 to -0.37) were also significantly lower at week 4 after acupuncture. Conclusion. This study highlighted that the acupuncture could significantly improve the overall therapeutic effect of PDS patients, alleviate the symptoms of postprandial fullness and early satiety, and improve the quality of life of patients. Our results supported that acupuncture was an effective therapeutic strategy for postprandial distress syndrome.